The ethnic penalty : immigration, education, and the labour market - Hasmath, Reza (Ashgate, 2012)
The Ethnic Penalty argues that a penalty has impeded the occupational success of ethnic minorities during the job search, hiring and promotion process. In this context, the book examines whether explanatory factors such as discrimination, an individual's social network, a firm's working culture, and a community's social trust are major contributing reasons behind this apparent penalty, whilst also making suggestions for improvement for visible ethnic minorities.